Modeling Disorder in Pyrochlores and Other Anion-Deficient Fluorite Structural Derivative Oxides - Kocevski, V.; Pilania, G.; Uberuaga, B. P. (Frontiers in Chemistry, 2021)
Their very flexible chemistry gives oxide materials a richness in functionality and wide technological application. A specific group of oxides that are related to the fluorite crystal structure, termed fluorite structural derivatives with pyrochlores being the most notable example, has been shown to exhibit a diversity of useful properties. For example, the possibility to undergo a transition from an ordered to disordered state allows these oxides to have high radiation tolerance. Atomistic-scale calculations in the form of molecular dynamics (MD) and density functional theory (DFT) have been extensively used to understand what drives this order/disorder transition. Here we give a brief overview of how atomistic-scale calculations are utilized in modeling disorder in pyrochlores and other fluorite structural derivatives. We discuss the modeling process from simple point defects to completely disordered structures, the dynamics during the disordering process, and the use of mathematical models to generate ordered solid-solution configurations. We also attempt to identify the challenges in modeling short range order and discuss future directions to more comprehensive models of the disordered structures.